Desmoid Tumor of the Popliteal Fossa during Pregnancy. (5th February 2015) - Weschenfelder, Wolfram; Lindner, Robert; Spiegel, Christian; Hofmann, Gunther Olaf; Vogt, Matthias
Abstract : Desmoid tumors are fibroblastic neoplasms that have an intermediate behavior with a highly aggressive infiltrative growth arising from deep muscle or aponeurosis. We present the case of a 34-year-old woman that developed a painless mass in the right popliteal fossa during pregnancy after intracytoplasmic sperm injection and hormonal therapy. The MRI scan showed a hyperintense mass of 6, 7 cm × 4, 7 cm × 3, 8 cm surrounding the lateral head of the gastrocnemius muscle. The open biopsy was done one week after delivery, and the histology showed a desmoid tumor. We performed the resection one week later and found the common peroneal nerve completely surrounded by the tumor. The close resection due to the neurolysis was the reason why an adjuvant radiation with 56 Gy was done. The last clinical examination, 18 month later, did not show any signs of recurrence and an excellent functional outcome. This case demonstrates the possible influences of pregnancy and hormonal therapy on the evolution of desmoid tumors.